Genomic complexity is associated with epigenetic regulator mutations and poor prognosis in diffuse large B-cell lymphoma. (1st January 2021) - You, Hua; Xu-Monette, Zijun Y.; Wei, Li; Nunns, Harry; Nagy, Máté L.; Bhagat, Govind; Fang, Xiaosheng; Zhu, Feng; Visco, Carlo; Tzankov, Alexandar; Dybkaer, Karen; Chiu, April; et al.
ABSTRACT: Diffuse large B-cell lymphoma (DLBCL) is the most common type of lymphoma with high mutation burdens but a low response rate to immune checkpoint inhibitors. In this study, we performed targeted next-generation sequencing and fluorescent multiplex immunohistochemistry, and investigated the clinical significance and immunological effect of mutation numbers in 424 DLBCL patients treated with standard immunochemotherapy. We found that KMT2D and TP53 nonsynonymous mutations (MUT) were significantly associated with increased nonsynonymous mutation numbers, and that high mutation numbers (MUT high ) were associated with significantly poorer clinical outcome in germinal center B-cell-like DLBCL with wild-type TP53 . To understand the underlying mechanisms, we identified a gene-expression profiling signature and the association of MUT high with decreased T cells in DLBCL patients with wild-type TP53 . On the other hand, in overall cohort, MUT high was associated with lower PD-1 expression in T cells and PD-L1 expression in macrophages, suggesting a positive role of MUT high in immune responses. Analysis in a whole-exome sequencing dataset of 304 patients deposited by Chapuy et al. validated the correlation of MUT- KMT2D with genomic complexity and the significantly poorer survival associated with higher numbers of genomic single nucleotide variants in activated B-cell–like DLBCL with wild-type TP53 . Together, these results suggest that KMT2D inactivation or epigenetic dysregulation has a role in driving DLBCL genomic instability, and that genomic complexity has adverse impact on clinical outcome in DLBCL patients with wild-type TP53 treated with standard immunochemotherapy. The oncoimmune data in this study have important implications for biomarker and therapeutic studies in DLBCL.